GDI engine operation with ethanol/gasoline blends and aqueous ethanol - Stone, R; Chen, L; Hinton, N; Leach, F; Xu, F (State Key Laboratory of Automotive Safety and Energy, 2012)
Ethanol is being promoted as a renewable fuel and as a means of improving energy security. The blends of gasoline and ethanol from 0 – 100 % ethanol were studied to evaluate their spray characteristics, combustion performances, and particulate emissions with blends of ethanol and water with up to 40 % water by volume being tested to research the combustion performances of different water ethanol blends and the miscibility of water with ethanol/gasoline blends using ternary phase diagrams for gasoline, ethanol, and water. The results show that presence of water in ethanol/gasoline mixtures is not an impediment to their use as a fuel in gasoline direct injection (GDI) engines. Adding ethanol to gasoline increases the injected fuel volume and the persistence of the fuel sprays, especially for a cold engine, leads to reduced mixture homogeneity, a decrease in the combustion stability, and an increase in particulate matter emissions for a stoichiometric mixture. Adding water to ethanol further increases injected fuel volume, but the increase in combustion duration and reduction in combustion stability are not significant with up to 30 % water by volume.